2012
DOI: 10.4103/0973-029x.102481
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of mast cells and vascular endothelial proliferation in oral precancerous lesion-leukoplakia

Abstract: Background:Oral leukoplakia is the best-known precursor lesion. Although a morphologic feature of oral epithelial dysplasia is well described, less is known about the pathobiologic changes within the cells and over the cell surfaces for malignant transformation.Aims:The present study is aimed at comparing and correlating the mast cell density (MCD) and micro vascular density (MVD) in Normal Mucosa (NM) and different grades of dysplasia and to analyze their role in disease progression.Materials and Methods:MCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
4
14
0
1
Order By: Relevance
“…This suggests that the angiogenic phenotypic change could occur mainly in OSCC rather than OED. 9 Other authors such as Sathyakumar et al 32 Basnaker et al 33 also studied MVD in samples with NOM, OED and OSCC diagnoses, but used different types of markers for blood vessels. However, it should be noted that most of the studies, independent of the marker used, coincide with the results of this study in relation to the increase in MDV in the transition from NOM to OED to OSCC.…”
mentioning
confidence: 99%
“…This suggests that the angiogenic phenotypic change could occur mainly in OSCC rather than OED. 9 Other authors such as Sathyakumar et al 32 Basnaker et al 33 also studied MVD in samples with NOM, OED and OSCC diagnoses, but used different types of markers for blood vessels. However, it should be noted that most of the studies, independent of the marker used, coincide with the results of this study in relation to the increase in MDV in the transition from NOM to OED to OSCC.…”
mentioning
confidence: 99%
“…Sathyakumar et al 13 observed a direct relationship between the density of mast cells and blood vessels when comparing normal mucosa to leukoplakia with and without dysplasia, showing progressive increases in density, being lowering in normal oral mucosa and higher in lesions with dysplasia. Despite the fact that there is a positive correlation between these histological components, Ali Tahir et al 14 believed that it is not direct since it is not only the mast cells that release proinflammatory enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the author concluded that the number of MCs and microvessel can be used as indictors of disease progression. [ 19 ]…”
Section: Mcs In Nommentioning
confidence: 99%